Physicochemical Properties of MTA and Portland Cement after Addition of Aloe Vera - Borges, Alvaro Henrique; Guedes, Orlando Aguirre; Volpato, Luiz Evaristo Ricci; Siebert Filho, Gilberto; Borba, Alexandre Meireles; Zina, Omar; Piva, Evandro; Estrela, Carlos (Iranian Endodontic Journal, 2017)
Introduction: The aim of this in vitro study was to determine the liquid-powder ratio, setting time, solubility, dimensional change, pH, and radiopacity of white structural and non-structural Portland cement, ProRoot MTA and MTA Bio, associated with a 2% glycolic solution containing Aloe Vera, as vehicle. Methods and Materials: Five samples of each material were used for each test, according to the American National Standards Institute/American Dental Association (ANSI/ADA) specification No. 57. Statistical analyses were performed using ANOVA and Tukey’s test at 5% significance. When sample distribution was not normal, non-parametric analysis of variance and the Kruskal-Wallis test were used (α=0.05). Results: No statistical differences were found in liquid-powder ratios among the tested materials. ProRoot MTA showed the longest setting time. Dimensional change values were acceptable in all groups. Also, no significant differences were found in pH values and pH was alkaline in all samples throughout the experiment. Mean radiopacity results obtained for white Portland cements did not meet ANSI/ADA requirements, and were significantly lower than those obtained for MTA-based cements. Finally, Portland cements showed significantly higher mean solubility values compared to the other samples. Conclusion: The physicochemical properties of the tested materials in association with Aloe Vera were compatible with ANSI/ADA requirements, except for the white Portland cements, which failed to meet the radiopacity specification. Keywords: Aloe Vera; MTA; Physicochemical Properties; Portland Cement